Aggregate Information and Organizational Structures. (6th April 2023) - Celik, Gorkem; Shin, Dongsoo; Strausz, Roland
Abstract : We study information flows in an organization with a top management (principal) and multiple subunits (agents) with private information that determines the organization's overall efficiency. Under centralized communication, eliciting the agents' information may induce the principal to manipulate aggregate information, which obstructs an effective use of information. Under hierarchical communication, the principal concedes more information rent due to loss of control, but is able to use the agents' information more effectively. The trade‐off between the organizational structures depends on the likelihood that the agents are efficient. Centralized communication is optimal when such likelihood is low. Hierarchical communication, by contrast, is optimal when it is high.